KERJASAMA UN WOMEN DAN NATIONAL COUNCIL FOR WOMEN DALAM MENINGKATKAN PARTISIPASI POLITIK PEREMPUAN DI MESIR (2017-2022) - Andrea Aletta (2023)
Full and effective political participation by women including in matters of human rights, inclusive growth and sustainable development. The political empowerment of women is an essential condition for democratic governance and can be measured both in terms of the legal rights granted to women to be able to vote, express opinions, and stand for elected office as well as in the practical exercise of these legal rights. Egypt is one of the countries in the Arab world that still adheres to patriarchal traditions. Egypt has taken several steps in recent years to adapt and reform its legal and policy frameworks to support women's political participation. Egypt has established various institutions in accordance with Article 214 of the 2014 Constitution, one of which is the National Council for Women (NCW). NCW was founded in 2000 to consolidate all national efforts on gender equality and women's empowerment. The low level of women political participation in Egypt then attracted the attention of the International Organization, UN Women, to help NCW in increasing women's political participation. UN Women is a United Nations organization dedicated to gender equality and women's empowerment.